Pathogenetic Characteristics of Anemia in Patients with Solid Tumors - VT Sakhin; ER Madzhanova; EV Kryukov; AV Sotnikov; AV Gordienko; OA Rukavitsyn (Клиническая онкогематология)
Aim. To study the impact iron metabolism disturbances and cytokine levels on the development of anemia in patients with solid tumors.